Molecular Adsorption of Silane on Ge, Ga and Al-doped CNT Structures: A Density Functional Theory Study - Baydir, Enver; Altun, Aycan; Fellah, M. Ferdi (Maik Nauka/Interperiodica/Springer, 2022)
The adsorption of silane molecule on the pristine CNT structure and metal-doped (Ge, Ga and Al) CNT (4,0) structure were investigated by DFT (density functional theory). Adsorption enthalpy, energy, chemical potential, chemical hardness values and electronic properties of CNT structures were obtained and reported. All metal-doped CNT structures gave more negative adsorption energy values for silane adsorption compared to the pristine CNT structure. The adsorption enthalpy energy value for silane adsorption on Ga doped CNT was calculated as -31 kJ/mol. In other words, the Ga-doped CNT structure may be a suitable material for silane adsorption with high adsorption energy change as a negative value. It was also investigated whether metal-doped and pristine CNT structures act as sensors for silane. In this study, metal-doped CNT structures examined show high adsorption properties but not sensor properties.
Keywords: silane; CNT; DFT; adsorption; sensor